Feasibility of using Determine TB-LAM to diagnose tuberculosis in HIV-positive patients in programmatic conditions: a multisite study. Issue 1 (1st January 2019) - Mathabire Rucker, Sekai Chenai; Cossa, Loide; Harrison, Rebecca E.; Mpunga, James; Lobo, Sheila; Kisaka Kimupelenge, Patrick; Mandar Kol'Ampwe, Felix; Amoros Quiles, Isabel; Molfino, Lucas; Szumilin, Elisabeth; Telnov, Oleksandr; Ndlovu, Zibusiso; et al.
ABSTRACT: Background : Determine TB-LAM is a urine-based point-of-care assay for diagnosis of tuberculosis (TB). Objective : To assess the feasibility of using LAM to diagnose TB in adult HIV-positive patients in resource-limited settings. Methods : We performed a multi-centric mixed-methods cross-sectional descriptive study in the Democratic Republic of Congo, Malawi, and Mozambique. We used the study and program monitoring tools to estimate user workload, turn-around time (TAT), and proportion of patients with LAM and sputum-based results. We conducted semi-structured interviews to assess the user acceptability of the LAM. Results : The duration of the LAM testing activity per patient was 27 min (IQR 26–29); staff continued with other duties whilst waiting for the result. More patients had a LAM versus a sputum-based result: 168/213 (78.9%) vs 77/213 (36.1%), p < 0.001 in DRC; 691/695 (99.4%) vs 429/695 (61.7%), p < 0.001 in Malawi; and 646/647 (99.8%) vs 262/647 (40.5%), p < 0.001 in Mozambique. The median TAT in minutes when LAM was performed in the consultation room was 75 (IQR 45–188) in DRC, 29 (IQR 27–39) in Malawi, and 36 (IQR 35–41) in Mozambique. In comparison, the overall median TAT for sputum-based tests (smear or GeneXpert) was 2 (IQR 1–3) days. The median time to the first anti-TB drug dose for LAM-positive patients was 155 (IQR 90–504) minutes in DRC and 90 (IQR 60–117) minutes in Mozambique. The overall inter-reader agreement for the interpretation of the LAM result as positive or negative was 98.9%, kappa 0.97 (95%CI 0.96–0.99). Overall, LAM users found the test easy to perform. Major concerns were use of the reading card and the prior requirement of CD4 results before LAM testing. Conclusion : It is feasible to implement the LAM test in low resource settings. The short TAT permitted same day initiation of TB treatment for LAM-positive patients.